Europe of Networks or the European Public Sphere? Four plus One Approaches - Nieminen, Hannu (Sociologija. Mintis ir veiksmas, 2015)
The main argument in this article is that instead of attempting to establish the existence or the non-existence of the European public sphere or public spheres, we could think of Europe as consisting of a multiplicity of networks, each having a public sphere or spheres of their own. The idea of seeing the public sphere from the point of view of networks is critical to the traditional Habermasian idea of conceiving the public sphere as something intrinsically restricted to national boundaries. The social and cultural networks operate in all areas of life. They have developed, transformed, and vastly expanded in time. It is difficult to make clear distinctions between different networks today as they can operate locally, nationally, trans-nationally, regionally, trans-regionally as well as globally. However, from the point of view of democratic theory it is still important to make a separation between these different spatial embodiments of the networks as they all indicate different modalities for democratic polities. Democracy needs to be thought differently on a local or national scale than on the trans-national or global scale. The idea of seeing the public sphere from the point of view of networks is critical to the traditional idea of conceiving the public sphere as something intrinsically restricted to national boundaries.